Growth Performance of Broiler Chickens Fed with Varying Levels of Cacao (Theobroma cacao) Bean Shell - Jose Jr. Obedencio; Reynaldo Intong; Maria Luz Soriano; Niňa Mae Villar; Imelda Hebron; Nena Siaboc (Universitas Airlangga, 2026)
Background: Interest in alternative agro-industrial by-products for poultry nutrition has been prompted by the high cost of conventional feed. Cacao bean shells (CBS) derived from roasted, unfermented cacao beans, a by-product of cacao processing, may serve as a sustainable feed ingredient for broiler chickens. Purpose: Evaluated in this study were the effects of graded levels of sun-dried roasted CBS on the growth performance and feed efficiency of broiler chickens under tropical production conditions. Method: Proximate analysis was conducted on CBS processed using three methods: air-dried (ADC), sun-dried with hot water treatment (HWC), and sun-dried only (SDC). For the feeding trial, a total of 120 unsexed, two week old broiler chickens were randomly assigned to four isonitrogenous and isocaloric dietary treatments containing 0% (control), 5%, 10%, and 15% sun-dried CBS. Monitoring of body weight gain, feed intake, and feed conversion ratio was performed throughout the experimental period. Results: No significant differences among processing methods were shown by proximate analysis (p> 0.05). Lower total weight gain and average daily gain were observed in birds fed 5% CBS compared to the control, while a progressive decrease in feed intake was recorded with higher CBS inclusion levels. Although numerical variation was noted in the FCR, no significant differences were identified. Conclusion: Inclusion of sun-dried roasted CBS in broiler diets at low levels (up to 5%) can be achieved without major deleterious effects on growth performance. Reduced growth was observed at higher inclusion levels, likely attributable to increased fiber content and effects on feed palatability. Further investigation is required to assess amino acid composition, nutrient digestibility, and anti-nutritional factor content to optimize the utilization of CBS in broiler diets.